The Effects of Quality Management System, Management Information Technology on Work Culture at Adventist Junior High School Bandung - Yossi Yostiani; Edi Suryadi; Suwatno Suwatno (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
Abstract: This study aims to examine the effect of Quality Management System and Management Information Technology on Work Culture at Adventist Junior High School Bandung. The research variables consist of independent variables, namely SMM and TIM, and the dependent variable, namely Work Culture. The research method used was a quantitative approach with a questionnaire instrument. Data were collected from 37 respondents who are educators at Adventist Junior High School Bandung. Validity and reliability tests were conducted to ensure the instruments used were valid and reliable. Furthermore, classical assumption tests (normality, heteroscedasticity, and multicollinearity tests) were conducted to ensure that the data qualified for linear regression analysis. The results showed that Quality Management System and Management Information Technology have an influence on Work Culture with a significance value of 0.033 and 0.002 (p < 0.05) and an R-Square value of 0.277, which means that 27.7% of variability in Work Culture can be explained by the use of QMS and TIM The research instruments were also declared valid and reliable, with the validity test results showing r-count > r-table and reliability test. The implications of this study suggest that the implementation of SMM and TIM in schools can enhance a more efficient and adaptive Work Culture. The findings are important for school managers to consider further investment in SMM management and TIM infrastructure in continuous training for educators to maximize the benefits of technology in creating a productive and innovative work environment. This research also enriches the literature on the central role of SMM and TEAM in shaping Work Culture in the education sector. Keywords: Quality Management System, Management Information Technology, Work Culture